Preparation Materials for Teacher's Training and Various Types of Training (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
the structure of the training session, the elements of the training session, the type of the training session, the teaching methodology, the stages of preparation for the training session and the types of training are mentioned